O siafi gerencial como instrumento de controle das despesas realizadas com material de consumo no instituto federal de São Paulo - Umeda, Sergio Hissashi [UNIFESP] (2015)
This work was developed with the purpose of analyzing the SIAFI Management as an instrument of control of the costs of consumables at the Federal Institute of São Paulo (IFSP), more specifically the expenditures budgeted, committed, settled and paid consumables in ten campuses the twenty-three campuses of the Federal Institute of São Paulo in 2012. The ten campuses are: Sao Paulo, São Roque, San Carlos, Sertaozinho, Cubatao, Braganca Paulista, São João da Boa Vista, Guarulhos, Caraguatatuba and Salto, which match the first decentralized units IFSP. Initially it showed that the Operating SIAFI provided segmented data difficult to manage and had to organize them. After this scenario the National Treasury developed the SIAFI Management (SG), as an improvement proposal. The methodological approach chosen for the conduct of research underwrote in the data collection and adopted the analysis of the reports generated by the system. The results presented by SG extracted from the reports proved to be effective for the analysis performed by the management in monitoring and control of budget credits, helping to improve the planning of the actions of IFSP members campuses.